Research on Polarization and Phase Fading Compensation in Michelson Interferometer Based on 3 × 3 Coupler and Novel Probe with Built-in Faraday Rotator - Shuaiqi Jing; Jian Rong; Jiayan Tian (Applied Sciences, 2019)
A self-designed probe and a feedback control scheme based on the Michelson interferometer with a 3 × 3 fiber coupler are proposed. A 45° Faraday rotator is built into the self-designed probe, and a feedback control scheme is used to judge the direction of increase or decrease for the phase compensation, so as to solve the problems of polarization and phase fading. In addition, a result-normalized method is applied in a micro-vibration measurement experiment. The experimental interferometer system achieves a high frequency of 1 MHz micro-vibration. The normalized results keep stable with a maximum deviation from the mean of 1.9% when the power of light reflected back into the self-designed probe is altered. Applied research is carried out by detecting the displacement due to a photoacoustic wave. Therefore, the experimental interferometer system is available for the practical application of micro-displacement measurements, noncontact high-frequency detection, and point-by-point image scanning in biological tissue.